2019
DOI: 10.1038/s41598-019-55438-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension in southwestern China

Abstract: This study investigated the prevalence, awareness, treatment, and control of hypertension and associated factors among urban adults in southwestern China. The study was conducted from 2013–2014 and used a multistage cluster sampling method to select a representative sample of 11,517 people in southwestern China, aged 35–79 years. Hypertension was defined as either systolic blood pressure of 140 mmHg or greater, diastolic blood pressure of 90 mm Hg or greater, or self-reported current treatment for hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 27 publications
12
30
1
Order By: Relevance
“…The prevalence of hypertension in our study was almost similar to these studies. Our findings on prevalence of hypertension was consistent with most of the global data and neighbouring countries [3,26]. However, a population based study from Ethiopia reported the prevalence of hypertension of 43% at the age 60 to 69 years and 49.3% at the age 70 years and above [3,26].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of hypertension in our study was almost similar to these studies. Our findings on prevalence of hypertension was consistent with most of the global data and neighbouring countries [3,26]. However, a population based study from Ethiopia reported the prevalence of hypertension of 43% at the age 60 to 69 years and 49.3% at the age 70 years and above [3,26].…”
Section: Resultssupporting
confidence: 91%
“…There is a lack of data on the awareness of hypertensive retinopathy on a population level. Studies have reported low awareness also for hypertension globally [3,26]. This finding highlights the need for awareness campaigns that target populations with high rates of hypertension.…”
Section: Resultsmentioning
confidence: 93%
“…This study also analyzed the correlation between dyslipidemia and various factors. In addition to the common risk factors associated with dyslipidemia 10,24 , such as smoking, hypertension, and diabetes, this study also showed a positive correlation between a high school degree or above, a monthly income of more than 2000 yuan, and the prevalence of dyslipidemia. This may be due to the better economic and nutritional status of people with higher education and income 25 .…”
Section: Discussionsupporting
confidence: 53%
“…Despite its large population and high GDP, Southwest China had a low-ranking number of percutaneous coronary intervention 23 . Interestingly, contemporaneous studies 24,25 showed that the prevalence of hypertension(38.4%) and diabetes 19.5% in the Southwest was no lower than the national average hypertension 32.5% 26 ,diabetes 9.7% 27 . Therefore, it is reasonable to speculate that the low prevalence of dyslipidemia and low LDL-C contribute to the lower ASCVD prevalence in southwest China.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol has been published, approved by the ethics committee of the Second People’s Hospital of Chengdu (NO 2013015), the methods in the study were in accordance with relevant guidelines, and a written informed consent was obtained from all participants 42 . Using three-stage (district-subdistrict-community) sampling procedures, five representative urban communities were randomly selected from five districts, including Jinjiang, Qingyang, Longquan district in Chengdu, and Yubei, Jiangbei district in Chongqing.…”
Section: Methodsmentioning
confidence: 99%